Pengaruh Green Marketing terhadap Ekuitas Merek Aqua dan Intensi Pembelian Konsumen - Widya Nur Hidayati; Hetty Karunia Tunjungsari (Jurnal Manajemen Bisnis dan Kewirausahaan, 2022)
There are important things that companies must pay attention to in developing environmentally friendly products, namely sustainability marketing. Sustainability marketing can be seen as learning about how business in product manufacturing is carried out from producing, selecting packaging materials, promotion, distribution, and how to consume the product. Danone-Aqua is a pioneer of bottled drinking water (AMDK) and soft drinks in Indonesia established in 1973. As a form of vision and commitment to managing the operations responsible socially and environmentally, Aqua Lestari develops initiatives that comprise the protection of water resources, reduction of CO2, optimization of packaging, packaging waste collection, and distribution of products sustainably. This type of research is quantitative with three variables: Green Marketing as an independent variable, Brand Equity as a mediating variable, and Consumer Purchase Intentions as the dependent variable. The data collection process is done by distributing instruments in the form of research questionnaires to 240 respondents who made purchases of Aqua AMDK. The result is that green marketing and Aqua’s brand equity have a positive and significant effect on consumer purchase intentions. Ada hal penting yang harus diperhatikan perusahaan dalam mengembangkan produk ramah lingkungan, yakni sustainability marketing. Sustainability marketing dapat dilihat sebagai pembelajaran tentang bagaimana usaha dalam pembuatan produk yang dilakukan dari memproduksi, pemilihan bahan packaging, promosi, pendistribusian hingga cara mengonsumsi produk tersebut. Danone-Aqua merupakan pelopor air minum dalam kemasan (AMDK) dan minuman ringan di Indonesia yang didirikan tahun 1973. Sebagai salah satu bentuk visi dan komitmen dalam mengelola operasional yang bertanggung jawab dalam sosial dan lingkungan, Aqua mengembangkan inisiatif Aqua Lestari yang terdiri dari perlindungan sumber daya air, pengurangan CO2, optimalisasi kemasan, pengumpulan sampah kemasan, dan distribusi produk secara berkelanjutan. Jenis penelitian ini adalah kuantitatif dengan tiga variabel, yakni Green Marketing sebagai variabel bebas, Ekuitas Merek sebagai variabel mediasi, dan Keinginan Membeli Konsumen sebagai variabel terikat. Proses pengumpulan data dilakukan melalui penyebaran instrumen berupa kuesioner penelitian kepada 240 responden yang melakukan transaksi pembelian AMDK Aqua. Hasilnya adalah green marketing dan ekuitas merek Aqua berpengaruh positif dan signifikan terhadap keinginan membeli konsumen.